Nonviolence, Peace, and Nonviolent Communication Towards a Holistic Framework for a Nonviolent World - Belinda F. Espiritu (International Society of Philosophy and Cosmology, 2023)
Humanity has been faced with violence of various gruesome forms such as the two world wars in the 20th century, the ongoing war between Israel and Hamas, the prolonged war between Russia and Ukraine, state-sponsored violence against its own people in the developing world, terroristic acts, gang fights, violent crimes, and other examples that result to death, destruction, and suffering. In this context, this paper examines the discourses on ethical principle of nonviolence and the application of the nonviolent communication with the goal of integrating these in peace communication. The study has a qualitative, inductive research design with the meta-analysis of research studies and discourses on the ethical principle of nonviolence and the effectiveness of nonviolent communication within the three spectra of peace, namely: inner peace, interpersonal peace, and outer peace (sociopolitical peace and peace with nature and the environment). The themes drawn from the research studies are agape love, compassion, ahimsa, application of Gandhian nonviolence in peacekeeping and peacebuilding processes, empathy, recognition of our own and the others' feelings and needs, conversion of peoples' hearts, changing oppressive social structures, and pacifist response to aggression. The study found the interconnection between inner peace and interpersonal peace, between interpersonal peace and outer peace, and between inner peace and outer peace. The study proposes a holistic framework integrating nonviolence and nonviolent communication principles in the three spectra of peace (inner, interpersonal, and outer) for teaching, research, and extension work.